Effect of a Structured Sensory Stimulation Program on the Sensory Function of Patients with Stroke-induced Disorder of Consciousness - Khadijeh Sargolzaei; Maryam Shaghaee Fallah; Nahid Aghebati; Habibollah Esmaily; MohammadTaghi Farzadfard (Mashhad University of Medical Sciences, 2017)
Background: About 50% of stroke patients suffer from the disorder of consciousness with such adverse effects as sensory deprivation. The provision of a care program consisting of simple and safe stimulations can prevent sensory deprivation and improve the patient's sensory function. Aim: This study aimed to determine the effect of structured sensory stimulation program on the sensory function of the patients with stroke-induced disorder of consciousness. Method: This randomized clinical trial was conducted on 80 patients with stroke-induced disorder of consciousness admitted to the Intensive Care Unit and Emergency Department of Ghaem Hospital, Mashhad, Iran, in 2016. The participants were randomly assigned into two groups of control and intervention. The patients in the intervention group were subjected to a sensory stimulation program consisting of auditory, visual, olfactory, gustatory, tactile, and motor stimulations for 14 consecutive days. The sensory function was measured every day before and after the intervention using the Sensory Modality Assessment and Rehabilitation Technique (SMART) instrument. On the other hand, the control group received the routine care. The data were analyzed in the SPSS version 11.5 using the Mann-Whitney test, Chi-square test, and independent t-test. Results: According to the results, the patients in the intervention and control groups had the mean ages of 66.2±8.9 and 63.8±10.8, respectively. The pre-intervention SMART scores of the two groups were homogenous (P=0.23). However, the independent t-test showed that the final SMART score was significantly higher (P